Role of Escherichia coli K capsular antigens during complement activation, C3 fixation, and opsonization. - Van Dijk, W C (1979)
Escherichia coli strains with K capsular polysaccharides are relatively resistant to phagocytosis by polymorphonuclear leukocytes, in contrast to E. coli strains without K antigens. This inhibition of phagocytosis is related to an impaired recognition of the K+ strains by the phagocytes due to ineffective opsonization. All five strains without K antigens were readily phagocytized after opsonization in 5% normal serum, compared with no uptake of the K+ strains. Evidence is presented that the decreased opsonization of the K+ strains in normal serum is caused by a low rate of complement activation of the strains, with subsequent absence of C3b fixation or C3d fixation or both to the cell wall of the bacteria. After removal of the K+ antigens by heating of a K+ E. coli strain, the strain was able to activate complement, to bind C3b or C3d or both, and to become opsonized. Complement was then activated via the classical and alternative pathways, which was comparable to the complement consumption by K- E. coli.